Underwear innovation for hemorrhoids patient - Setiyaningsih, Rani; Utami, Evi Dwi; Nugroho, Yopi Aji; Santosa, Agus (MEDISAINS, 2019)
Background: Symptoms experienced hemorrhoid sufferers are feeling pain in the anus, especially in sitting position. It is necessary to innovate special underwear which can reduce pressure on the anus and the pain experienced by the patientObjective: the study aimed to create and analyze special underwear for hemorrhoid sufferers which increased comfort and reduce the intensity of pain.Methods: This research imitated Research and Development (R&D). It consisted of 3 stages; stage I (literature study), stage II (product development) and stage III (product experiment).Result: The literature study in stage I obtained materials used to create special underwear for hemorrhoid sufferers by Cotton Combed 30s of 100% premium cotton and foam as a cushion. In the second phase of the research, designs and shapes were obtained. The results of product experiment in the third phase of the study discovered that respondents felt more comfortable by the special underwear than ordinary underwear and it was very effective in reducing pain.Conclusion: The innovation of hemorrhoid underwear is effective to increase comfort and reduce pain intensity in hemorrhoid sufferers.